Training on the Use of 3D Printing-Based Dummy Cakes and NFC as an Innovative Product Display at UKM Rayu Manis - Setiyoko, Nanang; Dewanto, Thomas Hahandry; Afandi, Haekal Ridho (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
Culinary SMEs have a significant contribution to national economic growth but still face challenges in marketing, particularly due to limited display space and insufficient provision of transparent product information. This community service program was carried out with UKM Rayu Manis through training on the use of 3D printing technology to produce dummy cakes and the integration of Near Field Communication (NFC) as an interactive medium for product information delivery. The method involved preparation, implementation, and evaluation stages, engaging owners and staff in practical training sessions. The results showed the creation of 10 PLA-based dummy cakes, with 7 units successfully equipped with NFC chips containing digital product information. The application of this innovation not only provides a more attractive and durable display alternative but also enhances information transparency and consumer interactive experience. Evaluation results indicated an average training score of 4.59, demonstrating high effectiveness in improving partner competence. Overall, this activity has proven relevant in strengthening digital marketing strategies, enhancing product display appeal, and supporting the competitiveness of culinary SMEs in the creative industry era.